The predictive effect of cultural orientation and perceived school climate on the formation of teachers’ growth mindsets - Zhang, Kai; He, Wu-jing (Frontiers in Education, 2024)
This study aimed to examine the predictive effect of cultural orientation and perceived school climate on the formation of teachers' growth mindsets. A total of 811 middle school teachers (26.88% females; mean age = 29.77) from Shanghai City, mainland China, participated in the study. The growth mindset inventory, Hofstede's cultural dimensions, and the school-level environment questionnaire were used to assess teachers' growth mindset beliefs, cultural orientations, and perceptions of school climates, respectively. Hierarchical multiple regression analyses were applied to test the hypothesized roles of teachers' cultural orientations and perceived school climates in predicting the formation of their growth mindsets. Two interesting findings were obtained. First, regarding the effect of cultural orientation, teachers' growth mindset belief was positively predicted by the Confucian dimension of cultural value in relation to long-term orientation but negatively predicted by the dimensions of power distance and uncertainty avoidance. Second, regarding the predictive effect of school climate, growth mindset was positively predicted by three school climate factors: school resources, decision-making, and instructional innovation. These findings provide empirical evidence for the perspectives of social cognitive theory and cultural and ecological psychology by highlighting the contextual sensitivity of growth mindset formation. These findings also have practical implications because they highlight the need to consider cultural and school climate factors in the promotion of teachers' growth mindsets.